The effects of weight fluctuation on the components of metabolic syndrome: a 16-year prospective cohort study in South Korea - Young Ran Chin; Eun Sun So (BMC, 2021)
Abstract Background Weight fluctuation (WF) is highly prevalent in parallel with the high prevalence of intentional or unintentional dieting. The health risks of frequent WF for metabolic syndrome (MS) have become a public health concern, especially for health care providers who supervise dieting as an intervention to prevent obesity-related morbidity or to improve health, as well as for the general population for whom dieting is of interest. The aim of this study was to investigate the long-term effect of WF on the risk of MS in Koreans. Methods This study analyzed secondary data from the Korean Genome and Epidemiology Study, a 16-year prospective cohort study, on 8150 individuals using time-dependent Cox regression. Results WF did not increase the risk of MS in either normal-weight or obese subjects. In an analysis of the components of MS, greater WF significantly increased the risk of abdominal obesity (HR = 1.05, 95% CI = 1.02-1.07, p < 0.001) in normal-weight individuals. However, WF did not increase the risk of hyperglycemia, low high-density lipoprotein cholesterol levels, elevated blood pressure, or raised fasting glucose in normal-weight individuals, and it did not influence any of the components of MS in obese individuals. Conclusion Since WF was found to be a risk factor for abdominal obesity, which is the most reliable predictor of MS, it should be considered when addressing weight control. Further studies on cut-off points for the degree of weight loss in a certain period need to be conducted to help clinicians provide guidance on appropriate weight control.